PENDAMPINGAN DALAM MENINGKATKAN MINAT BELAJAR SISWA DENGAN JOYFULL LEARNING METHOD DI SD NEGERI SIRING - Sarah Caesarani; Siti Meita Safira; Enjat Mardiyansah; Mohammad Rizki; Amir Ruslan (LPPM Universitas Bina Bangsa, 2022)
One of the Student Work Lectures (KKM) service programs held in the village of Sindang Karya, located at SD Negeri Siring, is a teaching and learning activity to increase student interest in learning. Implementation of the Student Work Lecture program in the village of Sindang Karya SD Negeri Siring which aims to increase student interest in learning with the Joyful Learning Method. So that the program can make the students of SD Negeri Siring more interested. While the method of implementing the Student Work Lecture Service (KKM) program includes fun learning where a learning process has a strong relationship between educators and students. The results of this Student Work Lecture (KKM) activity are: 1) Increasing student interest in learning, 2) Increasing student knowledge and 3) increasing student motivation to learn with the Joyful Learning Method. Thus, the service carried out by the Student Work Lecture Service Group (KKM) of Bina Bangsa University to Siring State Elementary School students in learning activities using the Joyful Learning Method has been well realized